2018
DOI: 10.1007/s10803-018-3835-z
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Relationship Between Autism Stigma and Informal Caregiver Mental Health

Abstract: Families play a crucial role in determining the mental health of the autistic individual(s) they are caring for. However, the stigma associated with autism can impair caregiver health. To investigate this, empirical evidence pertaining to stigma’s impact on informal caregivers’ mental health was systematically reviewed. All twelve included studies (n = 1442 informal caregivers) consistently reported the impact of autism related stigma upon caregiver mental health to be significant, meaningful and complex. A ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 48 publications
3
68
0
Order By: Relevance
“…In ASD research stigma is frequently reported as a barrier to seek help or to receiving a diagnosis (Grinker et al, 2012;Papadopoulos, Lodder, Constantinou, & Randhawa, 2019;Ruparelia et al, 2016;Zuckerman et al, 2014). This may be due to the fear of experienced shame, or the fear of a diagnostic label that has potential negative implications.…”
Section: Stigmamentioning
confidence: 99%
“…In ASD research stigma is frequently reported as a barrier to seek help or to receiving a diagnosis (Grinker et al, 2012;Papadopoulos, Lodder, Constantinou, & Randhawa, 2019;Ruparelia et al, 2016;Zuckerman et al, 2014). This may be due to the fear of experienced shame, or the fear of a diagnostic label that has potential negative implications.…”
Section: Stigmamentioning
confidence: 99%
“…Stigma experiences have been also reported in non-CLD groups, and it appears that stigma is a theme across different groups in the autism field. Papadopoulos et al (2019) carried out a systematic literature review exploring the relationship between autism-related stigma and the mental health of caregivers across diverse sociocultural settings, including countries in East Asia, the Middle East, USA, and Australia. The review showed that stigma has a harmful impact on the caregivers' mental health including depression, anxiety, and psychological distress.…”
Section: Stages Of Acceptance and Stigmamentioning
confidence: 99%
“…A recently published study (Kinnear et al 2016) with a sample of 502 families from USA and Canada showed that parents report that they experience stigma and that this adds to the difficulty of raising a child with autism. In addition, experiences of stigma related to having a child with autism can lead to social isolation and exclusion (Kinnear et al 2016) and to mental health difficulties (Papadopoulos et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…6 The consequences of such stigmatization include emotional trauma, mental and educational difficulties, and diminished self-perceptions. Caretakers and family members are also affected (e.g., feelings of isolation, social exclusion, guilt, extreme levels of distress, and lower subjective wellbeing), [7][8][9] increasing the risk of delayed intervention and developmental progress 10 or leading to avoidance of treatment altogether (i.e., label avoidance). 11 These outcomes are detrimental to those with the disorder and result in greater health care costs globally.…”
Section: Introductionmentioning
confidence: 99%